Ethnic differences in the relationship between step cadence and physical function in older adults. Issue 10 (19th May 2022) - McBride, Philip; Yates, Thomas; Henson, Joseph; Davies, Melanie; Gill, Jason; Celis-Morales, Carlos; Khunti, Kamlesh; Maylor, Benjamin; Rowlands, Alex; Edwardson, Charlotte
ABSTRACT: This study investigated associations between step cadence and physical function in healthy South Asian (SA) and White European (WE) older adults, aged ≥60. Participants completed the 60-s Sit-to-Stand (STS-60) test of physical function. Free-living stepping was measured using the activPAL3™. Seventy-one WEs (age = 72 ± 5, 53% male) and 33 SAs (age = 71 ± 5, 55% male) were included. WEs scored higher than SAs in the STS-60 (23 vs 20 repetitions, p = 0.045). Compared to WEs, SAs had significantly lower total and brisk (≥100 steps/min) steps (total: 8971 vs 7780 steps/day, p = 0.041; brisk: 5515 vs 3723 steps/day, p = 0.001). In WEs, 1000 brisk steps and each decile higher proportion of steps spent brisk stepping were associated with STS-60 ( β  = 0.72 95% CI 0.05, 1.38 and β  = 1.01 95% CI 0.19, 1.82, respectively), with associations persisting across mean peak 1 min ( β  = 1.42 95% CI 0.12, 2.71), 30 min ( β  = 1.71 95% CI 0.22, 3.20), and 60 min ( β  = 2.16 95% CI 0.62, 3.71) stepping periods. Associations were not observed in SAs. Ethnic differences in associations between ambulation and physical function may exist in older adults which warrant further investigationi.